Risk factors for hearing loss in infants under universal hearing screening program in northern Thailand - Watcharapol Poonual (2018)
© 2016 Poonual et al. Objective: To define the risk factors for hearing loss in infants (aged 3 months) under universal hearing screening program. Materials and methods: A total of 3,120 infants (aged 3 months) who underwent hearing screening using a universal hearing screening program using automated otoacoustic emission test between November 1, 2010 and May 31, 2012 in Uttaradit Hospital, Buddhachinaraj Hospital, and Sawanpracharuk Hospital (tertiary hospitals) located in Northern Thailand were included in this prospective cohort study. Results: Of the 3,120 infants, 135 (4.3%) were confirmed to have hearing loss with the conventional otoacoustic emission test. Five of these 135 infants (3.7%) with hearing loss showed test results consistent with auditory brainstem responses. From the univariable analysis, there were eleven potential risk factors associated with hearing deterioration. On multivariable analysis, the risk factors independently associated with hearing loss at 3 months were birth weight 1,500–2,500 g (risk ratio [RR] 1.6, 95% confidence interval [CI] 1.1–2.6), APGAR score ,6 at 5 minutes (RR 2.2, 95% CI 1.1–4.4), craniofacial anomalies (RR 2.5, 95% CI 1.6–4.2), sepsis (RR 1.8, 95% CI 1.0–3.2), and ototoxic exposure (RR 4.1, 95% CI 1.9–8.6). Conclusion: This study concluded that low birth weight, APGAR score < 6 at 5 minutes, craniofacial anomalies, sepsis, and ototoxic exposure are the risk factors for bilateral hearing loss in infants (aged 3 months) and proper tests should be performed to identify these risk factors. As an outcome, under the present circumstances, it is suggested that infirmary/physicians/general practitioners/health action centers/polyclinics should carry out universal hearing screening in all infants before 36 weeks. The public health policy of Thailand regarding a universal hearing screening program is important for the prevention of disability and to enhance people’s quality of life.